Atomic physics research at HIAF and future perspective. Issue 23 (January 2020) - Ma, X; Wen, W Q; Zhan, S F; Huang, Z K; Wang, H B; Yang, J; Zhu, X L; Yu, D Y; Cheng, R; Mao, L J; Yang, J C; Sheng, L N; et al.
Synopsis: A brief introduction to the undergoing HIAF projects in China is given, and the scientific goals as well as the atomic physics programs are discussed. A new science center in the Gulf area near Hongkong will pro-vide unprecedented opportunities for novel scientific researches based on large scale facilities.